Soil and Sediment Organisms as Bioindicators of Pollution - Samir Ghannem; Ons Bacha; Sondes Fkiri; Sabri Kanzari; Abdelwaheb Aydi; Samir Touaylia (Ecologies)
This review examines the role of soil and sediment organisms as bioindicators in environmental pollution assessment. As fundamental elements of terrestrial ecosystems, soils harbour a rich and diverse biodiversity that plays a key role in regulating ecological processes. The use of bioindicators provides a sensitive and specific approach to detecting the effects of chemical, biological, and physical pollutants on soil health. The review presents a detailed analysis of the types of contaminants commonly encountered, the soil organisms used as bioindicators, and the criteria for selecting the most appropriate bioindicators. It also discusses assessment methods, including soil sampling and analysis techniques, and the biological and ecological indices used to measure contamination. Regional case studies illustrate the practical application of bioindicators for assessing soil quality in different geographical contexts. The review also highlights current challenges to the use of bioindicators, such as technical limitations and the variability of organism responses, and suggests perspectives for future research, including technological innovation and the integration of bioindicators into environmental policy.